Penyuluhan kesehatan reproduksi sapi perah pada peternak sapi perah di Cipageran, Cimahi, Jawa Barat - Tyagita Hartady; Rini Widyastuti (ARSHI Veterinary Letters, 2019)
Cipageran, Cimahi city, West Java has a high population of dairy cattles and one of the suppliers of milk for the West Java region. However, there are limitations in farmers' knowledge about animal health, especially reproductive disorder. Data collection was carried out in the local dairy cattle farmer group. The method used were a pre-test on the reproductive health of dairy cattles, counseling on reproductive health and prevention of reproductive disorders, discussion related to the topic provided. Based on the results of the question and answer and discussion, information on the level of knowledge of the breeders' groups on the reproductive health of dairy cattles was obtained and efforts to prevent the emergence of reproductive disorders were good enough. However, the knowledge of farmers in order to prevent, handle and care for livestock is still lacking, so better support are needed.